2021
DOI: 10.1016/j.neo.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of Chloroquine and Panobinostat in ovarian cancer through induction of DNA damage and inhibition of DNA repair

Abstract: Ovarian cancer (OC) is the deadliest gynecologic malignancy, which is mainly due to late-stage diagnosis and chemotherapy resistance. Therefore, new and more effective treatments are urgently needed. The in vitro effects of Panobinostat (LBH), a histone deacetylase inhibitor that exerts pleiotropic antitumor effects but induces autophagy, in combination with Chloroquine (CQ), an autophagy inhibitor that avoid this cell survival mechanism, were evaluated in 4 OC cell lines. LBH and CQ inhibited ovarian cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…Previous reports from our group [ 3 ] and others [ 59 , 60 , 61 ] had already demonstrated that hydralazine and panobinostat were DNA damage-inducing agents. The mechanisms underlying the effect of panobinostat can be traced to its capacity to modulate DNA damage response (DDR) proteins [ 62 , 63 ] and to the induction of reactive oxygen species (ROS) [ 64 , 65 ], a characteristic that is shared with other HDACis [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports from our group [ 3 ] and others [ 59 , 60 , 61 ] had already demonstrated that hydralazine and panobinostat were DNA damage-inducing agents. The mechanisms underlying the effect of panobinostat can be traced to its capacity to modulate DNA damage response (DDR) proteins [ 62 , 63 ] and to the induction of reactive oxygen species (ROS) [ 64 , 65 ], a characteristic that is shared with other HDACis [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 94%
“…It has been described that some HDAC inhibitors, including Panobinostat, affect DNA DSB repair by inhibiting homologous recombination (HR) [ 32 , 40 , 41 , 42 ]. Indeed, we have recently reported that LBH inhibits the correct recruitment of Rad51 to DSB sites in OCCLs, which explains the HR defect [ 32 ]. However, the effect of HDAC inhibitors on DSB repair by NHEJ seems to be controversial [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…CQ has been demonstrated to exert pleiotropic cellular effects, including the generation of reactive oxygen species (ROS) [ 32 , 49 , 50 , 51 , 52 ]. We have recently shown that CQ-induced ROS production in OCCLs leads to the generation of DNA-DSBs [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations